PERKEMBANGAN JUDICIAL REVIEW DALAM SISTEM KETATANEGARAAN INDONESIA - Thaher, Irmanjaya (Gapenas Publisher, 2024)
Judicial review is a fundamental instrument in modern constitutionalism, upholding the supremacy of the constitution and protecting the fundamental rights of citizens. This mechanism ensures the hierarchy of legal norms and reflects a commitment to the principle of the rule of law in the Indonesian constitutional system.This study analyzes the development of judicial review in Indonesia through four dimensions: the historical-theoretical foundations in a comparative context, the dualism of authority between the Constitutional Court and the Supreme Court, reforms to mechanisms oriented toward constitutional supremacy, and the dynamics of judicial activism and their implications for the balance of the Indonesian constitutional system.The research method used a systematic, transparent, and structured Systematic Literature Review (SLR) to identify, evaluate, and synthesize relevant scholarly articles to obtain a comprehensive overview of conceptual developments and empirical findings.The research discussion shows that Indonesian judicial review is influenced by global legal traditions such as Marbury v. Madison and the theory of Hans Kelsen. The dualism of authority between the Constitutional Court and the Supreme Court creates inconsistent decisions that undermine legal certainty. The judicial review mechanism faces structural, procedural, and institutional weaknesses that require comprehensive reform through streamlining procedures, strengthening transparency, and increasing public participation.The Constitutional Court has developed as a progressive constitutional actor through judicial activism that shapes the national legal landscape. Integration of the judicial review system, reform of mechanisms oriented toward constitutional supremacy, and strengthening independence by establishing clear limits on constitutional authority are urgent agendas to realize an effective and reliable judicial review system that guarantees legal certainty for all Indonesian citizens.